1986
DOI: 10.7326/0003-4819-104-3-410
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Outcome from Intensive Care in Major Medical Centers

Abstract: We prospectively studied treatment and outcome in 5030 patients in intensive care units at 13 tertiary care hospitals. We stratified each hospital's patients by individual risk of death using diagnosis, indication for treatment, and Acute Physiology and Chronic Health Evaluation (APACHE) II score. We then compared actual and predicted death rates using group results as the standard. One hospital had significantly better results with 69 predicted but 41 observed deaths (p less than 0.0001). Another hospital had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
354
2
12

Year Published

1988
1988
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,110 publications
(393 citation statements)
references
References 23 publications
19
354
2
12
Order By: Relevance
“…Furthermore, accreditors and educators have emphasized teaching new core competencies (e.g., system-based practice) to promote quality and safety, but have given little guidance on the best educational strategies to employ 17,18 . Multidisciplinary teamwork training has the potential to improve patient safety and can help break down the traditional discipline-based silos that contribute to communication and teamwork failures [19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, accreditors and educators have emphasized teaching new core competencies (e.g., system-based practice) to promote quality and safety, but have given little guidance on the best educational strategies to employ 17,18 . Multidisciplinary teamwork training has the potential to improve patient safety and can help break down the traditional discipline-based silos that contribute to communication and teamwork failures [19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…Dans l'étude de référence de Knaus et coll. 4 , ils ont utilisé les scores APACHE pour comparer les taux de décès prédits et réels et se sont servis des résultats de groupes comme norme. Ils ont ensuite construit un palmarès des résultats institutionnels pour démontrer la supériorité de certains centres, et leurs caractéristiques, et, bien sûr, l'infériorité des autres.…”
Section: Les Systèmes De Nota-unclassified
“…Knaus et al's benchmark study 4 used APACHE scores to compare actual and predicted death rates using group results as the standard. The authors then constructed a ranking of institutional outcomes to demonstrate the superiority of some centres (and their characteristics) and, naturally enough, the inferiority of others.…”
mentioning
confidence: 99%
“…A seminal study conducted two decades ago 4 found that interaction and coordination amongst clinicians (medical and nursing staff) reduced patient deaths in ICU settings, but did not establish a link between nursing activities and patient outcomes. Since then a growing body of research indicates that RNs provide a continuous (24-h per day, 7 days per week) surveillance system for patients enabling the early detection and prompt intervention when their condition deteriorates.…”
Section: Nurse Staffing and Patient Outcomesmentioning
confidence: 99%